Role of interfacial tension on wettability-controlled fluid displacement in porous rock: A capillary-dominated flow and how to control it - Suparit Tangparitkul; Anupong Sukee; Jiatong Jiang; Chesada Tapanya; Nawamin Fongkham; Hongbin Yang (Capillarity, 2023)
Oil displacement by spontaneous imbibition is a capillary-governed process, in which wettability controls fluid displacement direction. Capillarity is a driving force to enhance oil displacement in water-wet system, while in oil-wet system capillarity is a resisting one. To promote oil displacement, the former requires high capillarity, but the latter opposes. Such requisites are hypothesized to be alternatively achieved by manipulating an oilwater interfacial tension, without altering wetting character. In this study, spontaneous imbibition was conducted with a set of specifically designed imbibing fluids. Brines at different valencies were meticulously selected to attain desired wettabilities: monovalent brine establishes a water-wetting while divalent brine provides an oil-wet characteristics. A non-ionic surfactant, Triton X-100, was intentionally chosen to solely reduce interfacial tension, with negligible change in wettability. By mixing each brine with the surfactant, high-interfacial tension and low-interfacial tension imbibing fluids at the same wettability for the two wetting regions were obtained, and hence the hypothesis can be examined. For water-wet system, reduced interfacial tension attributed to a weakened driving capillary force to oil displacement, and hence lower oil displaced. On the contrary in oil-wet system, reduction in resisting capillary force as contributed from a reduced interfacial tension displaced greater oil. The results demonstrate how the capillary-driven fluid displacement can be manipulated by the interfacial tension change only, without a challenge of altering wettability. With results obtained from both wetting regions, a correlation between capillarity and ultimate oil displacement was also observed. Document Type: Original article Cited as: Tangparitkul, S., Sukee, A., Jiang, J., Tapanya, C., Fongkham, N., Yang, H. Role of interfacial tension on wettability-controlled fluid displacement in porous rock: A capillary-dominated flow and how to control it. Capillarity, 2023, 9(3): 55-64. https://doi.org/10.46690/capi.2023.12.02